A New Method of Nice Knot Elastic Fixation for Distal Tibiofibular Syndesmosis Injury. Issue 3 (29th January 2023) - Zhong, Qigang; Zhan, Junfeng; Yang, Hu; Zhu, Nan; Feng, Ru; Yao, Yunfeng
Abstract : Objective: The distal tibiofibular syndesmosis (DTS) is a fretting joint and it is still a hot issue how to satisfy strong internal fixation while allowing fretting. This study described and evaluated a new method for elastic fixation of DTS injury with Nice Knot. Methods: The study was designed as a retrospective study. Between June 2020 and June 2021, 31 patients who were diagnosed with ankle fracture and DTS injury without additional orthopedic injuries were enrolled in this case series. The study included 22 males and nine females, with an average age of 34.71 ± 14.66 years. All patients were treated with Nice Knot binding for DTS. Surgical time, length of stay, time of DTS fixation, total weight‐bearing time, complications, imaging parameters, and functional scores at follow‐up were recorded. Paired sample t ‐tests or single factor analyses of variance were used at intra‐group comparison. Results: All patients completed surgery with normal syndesmotic parameters. The recovery of DTS injury was verified by Hook and lateral malleolus rotation tests. The average follow‐up time was 15.97 ± 3.30 months. Only one case showed superficial infection after surgery, and the wound healed after symptomatic treatment. In terms of imaging, there were no significant differences in tibiofibular clear space (TFCS), tibiofibular overlap distance (TFOS), medial clear space (MCS), and superior clear space (SCS) immediately and at different follow‐up points after surgery. All obtained excellent and good outcomes according to the AOFAS score at least follow‐up after surgery. Conclusions: Nice Knot elastic fixation of DTS injury is firm and stable while maintaining the physiological micromotion of the ankle joint. Abstract : Close to the anterior edge of the fibula, a bone tunnel was made with a diameter of 2.5 mm Kirschner wire, and a double‐strand polyester non‐absorbable suture was introduced from the outside to the inside. The medial double strands were pulled back with vascular forceps close to the posterior edge of the tibia, and Nice Knot was used on the lateral side of the fibula. A thread was held by both hands and pulled hard. After obtaining satisfactory tension, the knot was tightened through three single‐line knots. We find that Nice Knot elastic fixation of distal tibiofibular syndesmosis injuries is firm and stable while maintaining the physiological micromotion of the ankle joint.